Radical Humanism Selected Essays - Améry, Jean (Indiana University Press, 1984)
Radical Humanism gives English-language readers the opportunity to expand their acquaintance with one of the most penetrating intellects of the postwar era. Philosopher, novelist, activist, and cultural, literary, and political critic, Jean Amery (1912-78) was a man of passionate concerns and interests. The astonishing range of his thought is admirably represented in the twelve essays collected here for the first time. Drawing from Amery's works covering the period 1967-78, Sidney and Stella Rosenfeld have chosen essays that fall into the broad categories of autobiography; reflections on Judaism; history and politics; and examinations of other writer-philosophers. Each of the pieces demonstrates Amery's remarkable ability to discern the very essence of any subject to which he applies himself, be it a political trend, a historic event or movement, an epoch, a life, or a philosophy. Jean Amery was not only a brilliant thinker but a master stylist. All the strengths of his incomparable writing are preserved in the Rosenfelds' outstanding translation, which readers will find provocative, illuminating, and-always-powerful.